Aircraft testing in terms of methodology, safety and development of aircraft - Bilbija, Branko B. (Vojnotehnički glasnik / Military Technical Courier, 2016)
Aerospace as a whole, primarily aviation and planes, for a short time after 1903, greatly advance the frontiers of human activity. Initially, unsafe "flying device" the plane, has become a factor in ²loose² resolving wars and one of the reliable means of transport and communication between people around the world. Quick technical and technological development required a special approach. Mass production and use of aircraft, brought in light the need for standardization in the production, testing and lead into operational use of combat aircraft, as well as in commercial use for the purposes of air traffic. Testing the aircraft, is now more disciplinary research activity of a large number of experts from various fields, including test pilot who is an irreplaceable member. At that goal the test-measuring equipment (IMO), are specifically designed, and test pilots are trained in specialized schools for the experiment pilots.